2016
DOI: 10.1111/nin.12141
|View full text |Cite
|
Sign up to set email alerts
|

Engagement practices that join scientific methods with community wisdom: designing a patient‐centered, randomized control trial with a Pacific Islander community

Abstract: This article illustrates how a collaborative research process can successfully engage an underserved minority community to address health disparities. Pacific Islanders, including the Marshallese, are one of the fastest growing US populations. They face significant health disparities, including extremely high rates of type 2 diabetes. This article describes the engagement process of designing patient-centered outcomes research with Marshallese stakeholders, highlighting the specific influences of their input o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
(50 reference statements)
0
36
0
Order By: Relevance
“…After two years of engagement, which included a broad-based mixed methods study and multiple focus groups to document the community's top priorities, the community chose T2D as their top health concern and recommended a family approach to address T2D [76] . Over the past three years, our partnership has conducted several pilot studies related to diabetes beliefs and behaviors [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] . Consistent with CBPR principles [85] , development of the intervention, study design, and proposed evaluation and dissemination plans were conducted collaboratively between community and academic partners [76] , [83] .…”
Section: Methodsmentioning
confidence: 99%
“…After two years of engagement, which included a broad-based mixed methods study and multiple focus groups to document the community's top priorities, the community chose T2D as their top health concern and recommended a family approach to address T2D [76] . Over the past three years, our partnership has conducted several pilot studies related to diabetes beliefs and behaviors [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] . Consistent with CBPR principles [85] , development of the intervention, study design, and proposed evaluation and dissemination plans were conducted collaboratively between community and academic partners [76] , [83] .…”
Section: Methodsmentioning
confidence: 99%
“…The CBPR collaborative in northwest Arkansas began with a series of qualitative studies that indicated diabetes, obesity, and other cardiometabolic diseases were the primary health concern of the Marshallese [20, 2327, 30], but there was a lack of data on the prevalence and severity of non-communicable diseases within the northwest Arkansas Marshallese community. As the CBPR team sought to fill this gap in information, community collaborators explained Pacific Islanders’ health beliefs and behaviors reflect a collectivistic orientation in which church plays a crucial role [50, 51].…”
Section: Introductionmentioning
confidence: 99%
“…The Adapted‐Family DSME curriculum's cultural resonance could have encouraged participants to attend the intervention. The Adapted‐Family model was developed using an intensive CBPR process , and was adapted to include culturally appropriate components throughout the DSME curriculum. The increased exposure could also be because the intervention engaged the participant's family, and the engagement of family members in DSME improved participation.…”
Section: Discussionmentioning
confidence: 99%
“…The research team overcame this trauma and distrust through the use of a community‐based participatory research (CBPR) approach. The present research is a follow‐up to a randomized control trial (RCT) of diabetes self‐management education (DSME), undertaken by a CBPR partnership between the University of Arkansas for Medical Sciences (UAMS) and the Marshallese community in Arkansas .…”
Section: Introductionmentioning
confidence: 99%